In-source collision activated dissociation for coal/biomass-based model compounds and structural characterization of a coal extract. (15th December 2018) - Wang, Fei; Dong, Xueming; Fan, Xing; Zhao, Yun-Peng; Li, Guo-Sheng; Wang, Chu-Fan; Wei, Xian-Yong; Ma, Feng-Yun; Zhong, Mei
Highlights: Fragmentation patterns of 22 model compounds with varied energies were discussed. The optimal collision energy to investigate aromatic core structures should be 80 eV. Energy-resolved ISCAD showed potential for in-depth structural analysis of coal/biomass. Abstract: In-source collision activated dissociation (ISCAD) is an effective method to obtain molecular structure of coal and biomass and provide basic knowledge for coal/biomass conversion. Twenty two coal/biomass-based model compounds and one coal extract were studied via ISCAD to understand the relationship between collision energy and molecular structure and the application of ISCAD in the characterization of coal. Model compounds showed different fragmentation patterns with the increase of collision energy and the detailed fragmentation pathways in context of collision energies were proposed. According to the ISCAD results of coal extract, the weighted mean molecular weight (MW) and weighted mean double-bond equivalent (DBE) values of ionized coal molecules decreased over collision energy of 80 eV. The decrease of weighted mean MW and DBE were mainly caused by the cleavage of alkyl chains, bridged bonds, and minor cracking of small aromatic cores from precursor ions upon fragmentation. Therefore, the optimal ISCAD collision energy for the investigation of aromatic core structures of the coal extract should be around 80 eV.